Does the Politics of Recognition function as a mechanism for the amelioration of colonialism’s effects, or as a means through which these effects are reproduced? - Mcintosh, Monique (Kent Law Review, 2022)
The Politics of Recognition is a theory that provides a lens through which we can understand relations between two or more individuals, and its effect on one’s understanding of self. The struggle to be recognised by another individual shapes one’s identity, meaning that key aspects of one’s identity, such as self-worth, can only be present through positive recognition from others; this struggle to be recognised is what many recognition theorists deem to be the catalyst of social struggles and thus mutual recognition is central for a just society. The title therefore invites us to question whether the politics of recognition can be used in a context of postcolonialism[1] and adequately address and dismantle the remanences of colonialism, or whether this is a façade, and even if unbeknown, recognition is in fact a tool that works to reproduce the effects of colonialism. In such a context, I argue that although inaccurate recognition is a clear effect of colonialism, ‘proper’ recognition cannot eradicate such effects. I argue that to suggest that it does, would be to disregard and oversimplify the complexities and power structures at play in post-colonial contexts. In order to illustrate this, I will firstly be addressing the arguments of those who argue that recognition can be a successful tool, and then highlight the shortcomings and limitations of such an argument. I will then go on highlight how exactly recognition in such a context is a counterproductive and a negatively reproductive tool. Finally, I will be highlighting what mechanism I would suggest as more appropriate to combat and dismantle the effects of colonialism.[2] Mechanism for the amelioration of colonialism’s effects The Politics of Recognition theory is grounded in Hegel’s Slave and Master dialect. Hegel illustrates the development of self-consciousness through the meeting of two people. Through this illustration Hegel depicts two independent ‘self-consciousnesses’ who engage in a life-and-death struggle. They struggle as they each see the other as a threat, as their understanding of themselves has shifted from objective to subjective. In light of such a shift each individual fights to the greatest extent to be able to understand their strength in relation to the other, whilst also trying to prove each’s worth to the other. Out of such a conflict a master/slave relationship is produced.[3] Solomon notes that through this idea Hegel is able to illustrate how the: “Human existence is primordially a matter of mutual recognition, and it is only through mutual recognition that we are self-aware and strive for the social meanings in our lives”.[4] Such a concept was then built upon, most distinctly by Charles Taylor who linked recognition to identity and freedom. Identity, which Taylor classes as understanding oneself and our defining characteristics, is partly shaped by recognition or its absence. The latter of which, misrecognition, can lead to a distorted understanding of oneself. Taylor goes on to say that misrecognition or non-recognition can be a form of oppression and imprisoning, resulting in a reduced mode of being barred from the freedom that recognition brings.[5] How this then links to contexts of post-colonialism can be seen in works such as those of Axel Honneth who argued that a leading motivation for social struggle is the feeling of shame, anger and rage felt when individuals believe they are not being recognised as they should. In light of this Honneth produces a three-stage illustration of three forms of recognition, with the latter two being relevant to issues of social struggle.[6] Firstly, a child gains self-confidence through their needs being met by the carer. Secondly, self-respect is developed upon gaining equal legal personalities as they are recognised as morally responsible. Thirdly, self-esteem is developed when one’s particular traits are recognised as valuable.[7] Honneth argues that going through these three stages provides a means where “one can be sure of the social value of one’s identity”, thus negating the need for conflict.[8] Through such understandings scholars have concluded that an adequate remedy to such social struggles, importantly including the effects of colonialism, is through recognition. Taylor himself noted that as a result of colonialism, imagery of inferiority and savagery have been projected onto the colonized people to the extent to which the colonised mind internalises such misrecognition and imagery, resulting in self-hatred. Taylor therefore concludes that to counter such a result: “due recognition is not just a courtesy we owe people. It is a vital human need”, as for Taylor, freedom can only be established when another recognises another for what they truly are.[9] Such an understanding of recognition can be understood as the ‘deficit model’.[10] This model, termed by Cillian McBride, approaches issues of oppression and injustice, which has clear parallels to the context of post-colonialism, with noting a distorted or lack of recognition. It proposes either: (a) expanding or adjusting current patterns of recognition, or (b) instantiating forms of recognition where they were previously withheld.[11] However, it will be argued that Taylor and Honneth’s deficit model of recognition, when applied to a context of post-colonialism, fails to grasp the complexities and nuances of context, and thus cannot adequately address the effects left by colonialism. Means through which the effects are reproduced As highlighted by McBride, the deficit model advocated for by Taylor and Honneth “offers a seriously truncated snapshot of relations of recognition. In particular, it diverts our attention away from questions of power and authority”.[12] This parallels the common critiques of Taylor’s and Honneth’s work in that it inadequately takes into account, or in fact completely negates, what takes place at the intersection of power and recognition, and how this affects one’s self awareness and identity-formation.[13] Although the politics of recognition may work to improve social issues in more neutral micro-contexts, in contexts of power, dominance, mental and physical objectification, like that of post-colonialism, such a technique only enforces and reproduces such effects whether such effects were intentional or not. The reason for such a stance that I will be exploring in this section can be summarised well in Audre Lorde’s quote: “For the master’s tools will never dismantle the master’s house.”[14], which characterises the sentiment of my argument. Such a stance was also held by Glen Sean Coulthard, who explored the ways in which since 1969 we have seen the “modus operandi of colonial power relations in Canada” move from an explicit and unconcealed structure of domination to forms of colonial governance that operates through the tool of state recognition and accommodation.[15] In order to establish such an argument Coulthard explores the work of Franz Fanon. In Fanon’s 1952 text Black Skin, White Masks, he challenges the applicability of Hegel’s slave/master dialect, established in my first section, to colonial and racialised contexts.[16] Through this Fanon concludes that in such contexts of domination, firstly the terms of recognition are generally orchestrated in the interests of the master, which in colonialism would translate into the state a dominating society. Secondly, slaves, or in this context the colonized, develop ‘psycho- affective’ attachments to master sanctioned forms of recognition, and such attachments are essential for maintaining the political and economic structure of master/slave (colonizer/colonized) relations.[17] In addition to this, Fanon addresses issues of Hegel’s mutual recognition in post-colonial contexts, or as Coulthard puts it ‘hegemonic and subaltern communities.’[18] The main issue in its application is that the mutual feature of dependency is rarely present in such contexts. Fanon makes this observation through stating that ultimately the colonial master “basically differs” from the master depicted in Hegel’s Phenomenology of Spirit. “For Hegel there is reciprocity,” but in the colonial context “…the master laughs at the consciousness of the slave. What he wants from the slave is not recognition but work”.[19] Therefore, as Coulthard notes, in colonial context the ‘master’ namely, the colonial state and dominant society, do not require recognition from the communities “…upon which its territorial, economic, and social infrastructure is constituted. What it needs is land, labour, and resources.”[20] Therefore, as opposed to conditions of reciprocated dialects of recognition, such dialectic either breaks down with the nonrecognition of equal status of the colonized, or, as Coulthard puts it “with the strategic ‘domestication’ of the terms of recognition leaving the foundation of the colonial relationship relatively undisturbed”.[21] Furthermore, as Fanon notes, recognition is based on the coloniser’s and its succussing state powers terms, Coulthard notes how such an insight can be demonstrated when we look to the Aboriginal rights movement in Canada. Coulthard highlights how the use of recognition has been constrained and limited by the state, courts, and policy makers in a way that allows the preservation of power dynamics and ‘the status quo’.[22] For example, in relation to the law, the Supreme Court of Canada has consistently refused to recognize Aboriginal people and as autonomous, ‘equal and self-determining’ individuals due to their adherence to precedents that are routed in white supremacy and enlightenment ideology, namely that indigenous communities are “too primitive to bear political rights when they first encountered European powers”.[23] For example, in Delgamuukw v. British Columbia it was held that any remaining Aboriginal rights that survived the assertion of the British Crown’s sovereignty could be infringed by the government as it could be shown to further “a compelling and substantial legislative objective” that is “consistent with the special fiduciary relationship between the Crown and the [A]boriginal peoples”.[24] Therefore, one has to question as to what objectives would justify an infringement, and surely this will be susceptible to exploitation? According to the Court, it could include almost any, including exploitative, economic venture, including the “development of agriculture, forestry, mining, and hydroelectric power, the general economic development of the interior of British Columbia, protection of the environment or endangered species, and the building of infrastructure and the settlement of foreign populations to support those aims”.[25] Therefore, it is clear that Fanon’s analysis is still indicative in a post-colonial context as the state will only recognise both the collective and individual rights of indigenous people to the extent that it does not infringe or disrupt the power dynamics of the relationship itself.[26] Another of Fanon’s observations of recognition in the coloniality context, is its relation to psychology and recognition’s ability to form a skewed perception of oneself, which I will explore further in the following section. I argue that such observations are still relevant and applicable upon application of post-colonial conditions. As proposed through the ‘deficit model’ such issues of misrecognition that effect one’s understanding of themselves can be rectified through corrective and accurate recognition. However, I argue that the issue with such a proposition is that it neglects to take into account that due to such internalisation of misrecognition therefore means that such individuals and communities demands are skewed and tainted by such internalisation, therefore prohibiting the needed recognition from being demanded. This is a point also noted by Taiaiake Alfred who states that such internalisation has: “…the ability to asymmetrically govern how Indigenous subjects think and act not only in relation to the recognition claim at hand, but also in relation to themselves, to others, and the land. This is what I take Alfred to mean when he suggests, echoing Fanon, that the dominance of the legal approach to self-determination has over time helped produce a class of Aboriginal ‘citizens’”.[27] Another way of compartmentalising how recognition works in contexts such as post colonialism where there are clear power dynamics at play is that of Jean-Paul Sartre whose work has clear parallels with Fanon and Coulthard, and through which we can see just how recognition in such a context only leads to the facilitation and reproduction of colonialism’s effects. Sartre argues that in such contexts recognition is a form of enslavement where one is ‘fixed’ by “the look of another”.[28] For Sartre, another individual “…is always a threat to my own experience of self, having the power to objectify me and cause me to flee into self-objectification”, and therefore the only solution to this is to “turn back” the gaze and objectification.[29] Therefore, for Sartre recognition is an ongoing power struggle, “a constant unending conflict between subjects who seek to make each other objects of the gaze as the precondition of claiming their inner freedom”.[30] He notes that in situations of unequal power dynamics this struggle does not take place, and illustrates this with the example of a Jew in an anti-Semitic society who does not have the opportunity to ‘turn back’ the gaze’ as they are what Sartre deems as ‘overdetermined’.[31] As such they are “not only objectified in the ontological sense of being for others – as the condition for his or her fundamental relation to others – but also as a Jew”.[32] Ultimately, the individual’s ability to gaze back is undermined, so that here the gaze works “unilaterally between the one who objectifies (the anti-Semite) and the one who is objectified (the Jew)”.[33] Here we can see clear parallels with the work of Fanon and Coulthard in the way that in such a context the colonized is denied the option to turn back the ‘gaze’, and is subjected and thus objectified to the gaze and thus the misrecognition of the coloniser or now dominant forces in power. Overall, it is clear that in contexts similar to that of colonialism and efforts to counteract its effects highlight how “…subordinating recognition relationships serve precisely to maintain hierarchies of perceived ontological security, such that some groups ‘enjoy a semblance of sovereign agency at others’ expense”.[34] What is an actual mechanism for the amelioration of colonialism’s effects? After establishing that due to the power structures at play the Politics of Recognition is not an adequate mechanism to analyse colonialism effects and allow a comprehensive critical discussion, it is worth addressing what would be an adequate mechanism. Therefore, in this section I will be highlighting proposed alternative techniques of ameliorating colonialism’s effects. This is largely involves paying attention to the power dynamics at play, as well as the associated underestimation of the power of self-recognition. Dale Turner Dale Turner suggests that if Indigenous people want their relationship with the Canadian State to be “informed by their distinct worldviews,” they will need to “‘engage the state’s legal and political discourses in more effective ways”.[35] Turner derives this remedy from the argument that the effects of colonialism are less to do with recognition and more to do with exclusion, in that the colonial power relations operate largely through excluding the perspectives of Indigenous individuals “from the discursive and institutional sites that give their rights content”.[36] Turner submits that the most productive way to rid of the power structures at play post-colonialism is for Indigenous people to find ways of “participating in the Canadian legal and political practices that determine the meaning of Aboriginal rights”.[37] The way in which Turner proposes that Indigenous people do this is through what he describes as ‘word warriors’, who are capable of engaging in both political and legal discourses.[38] Turner proposes this as he concludes that unfortunately, but also unavoidably, for the foreseeable future the rights of Indigenous people will be largely dictated and interpreted by “non-Indigenous judges and policy makers within non-Indigenous institutions”[39], therefore it is crucial that Indigenous people, such as though the purposed ‘world warriors’, are able to become “non-Indigenous judges and policy makers within non-Indigenous institutions”.[40] Turner states his proposition is distinct from and more suitable than those of other indigenous intellects, such as Patricia Monture and Taiaiake Alfred, who advocated that Indigenous people to “turn our backs” to the state.[41] Turner criticises such approaches as lacking in providing adequate tools needed to protect such individuals from the “unilateral construction of our rights by settler-state institutions” which only through participation can this be combated to “shape the legal and political relationship so that it respects Indigenous world views”. I argue the limitation to Turner’s argument is threefold. Firstly, though Turner, as mentioned, acknowledges that there is unequal power dynamics at play in such a context, he negates to apply this to the work of the ‘word warriors’. As highlighted by Coulthard in recognition of these power dynamics one has to question how such individual’s interjections and comments in these spaces would be heard and how much weight would be given to them.[42] Secondly, one also has to question the risk of such ‘word warrior’s’ interjections being influenced and shaped by the state. Turner himself notes this and states that: “The anxiety generated by moving between intellectual cultures is real, and many indigenous intellectuals find it easier to become part of mainstream culture. This kind of assimilation will always exist, and it may not always be a bad thing for indigenous peoples as a whole. It becomes dangerous when indigenous intellectuals become subsumed or appropriated by the dominant culture yet continue to act as if they were word warriors.”[43] However, although Turner states that Indigenous people must therefore remain grounded both in thought and practice to avoid such psychological infiltration, Turner’s short coming here is that it neglects to discuss sufficiently how this crucially would look like in practice, particularly as “they seek to interpolate the much more powerful discursive economy of the Canadian legal and political system”.[44] Finally, Turner fails to address the issue that is that the effects of large sectors of colonialism are outside of such political discourses and are “entwined with the economic, political, and military might of the state itself.” So adequate attendance has to be given to such issues through practices that “move beyond liberal and ideational forms of discursive transformation”. Nancy Fraser Another proposed alternative approach to the amelioration of the effects of colonialisms effects proposed by Nancy Fraser. Fraser proposes that contrary to the opinions of Taylor, only recognition coupled with redistribution would allow for justice in contexts of ill-balanced power dynamics, similar to those of post-colonialism[45]. She suggests that such a coupling would allow for “participatory parity”, meaning the guarantee that each individual has an equal participation in the public sphere.[46] They way in which Fraser reaches such a conclusion is through arguing that redistribution ensures the objective condition, whilst recognition to safeguard one’s intersubjective condition[47]. This is based on her understanding that injustices are based on economic exploitation and cultural disrespect that can be dealt with through redistribution and recognition retrospectively. Fraser notes that these two tools are interdependent and only through this two-dimensional theory can the complexities of injustices be addressed sufficiently. She argues this based on the reasoning that, firstly, if we were to apply redistribution singularly without considering relations of recognition, the receivers of such redistribution could be characterised and thus they themselves internalise depictions of themselves as “social parasites”.[48] Additionally, as already addressed in the previous section, Fraser again highlights the clear short fallings of using recognition singularly, particularly with its inability to gage all aspects of justice that then can lead to the worsening economic positions of such groups.[49] They way in which Fraser then perceives such a theory to work in practice is the distinction between affirmative and transformative remedies. The former, largely based on the singular application of the politics of recognition, “address unjust outcomes, conferring respect upon misrecognized groups or transferring resources to the underprivileged”[50] whereas transformative remedies based on Fraser’s dual factored theory allow for addressing the injustices’ “underlying generative framework” that produces the original unjust conditions, and therefore destabilise and alter hierarchies and relations of production.[51] Furthermore, Fraser states how such an approach allows for the avoidance of conflicting mechanisms of amelioration due to the distinctness of redistribution and recognition, thus avoiding the reinforcing of “‘the underlying structures that give rise to injustice, or to generate resentful political backlash”.[52] My critique of Fraser’s theory is that although her approach addresses a wider scope than recognition used as a tool singularly, it negates to account for the power relations in contexts of injustice. Those with power to conduct recognition or redistribution will largely have their own interests and security at heart, which largely rely on the maintenance of injustice. So, similar to Turner, it is hard to see how Fraser’s reformulation would overcome such a fundamental obstacle to any reformulation of recognition in a context similar to that of postcolonialism. Fanon In light of these shortcomings, the mechanism of amelioration that I find most attractive in its reasoning is the approach advocated by Fanon. Fanon takes a dual approach to ameliorating the effects of colonialism. Firstly self-recognition, and secondly, necessary and proportionate violence; each of which I will address in turn. Self-recognition With regards to self-recognition, Fanon notes in Black Skin, White Masks that the objectifying and alienating nature of intersubjective recognition in contexts of racial inequality results in a "suffocating reification," a "haemorrhage" resulting from the “fixed” violating “gaze” of another, that causes the colonized to fall into self-objectification.[53] The key issue for Fanon here is that such an individual “has no ontological resistance in the eyes of the white man”.[54] In light of this, Fanon argues that the common response to such self-objectification is to denounce the characteristics that place such an individual as an ‘other’, thus resulting in the desire “to be recognised not as black, but as white”[55] due to what he describes as an “inferiority complex”.[56] In order to combat this, Fanon puts forward his branch of the negritude movement, namely that internalised racism can be combatted by “reinscribing value and worth to those identity-related differences that colonial discourse had hitherto characterized as savage, dirty, and evil”.[57] The way in which Fanon went about doing this was through finding and studying ‘black antiquity’ and what he "discovered left [him] speechless[58]". Through such discoveries, Fanon learnt that the image projected and internalised by colonised individuals was wholly incorrect and, in fact, specifically for black people, they were not "primitive or subhuman" but belonged civilizations in their own right with their own traditions, history, values and achievements.[59] Such discoveries left Fanon feeling empowered and mobilized a sense of self-worth that recognition from the dominant forces in society would not be able to deliver and in fact largely contradict. Therefore, Fanon concludes that "Since the Other was reluctant to recognize me, there was only one answer: to make myself known.”[60] The reason as to why this is so critical for the amelioration of colonialism’s effects is that a restructure of social relations cannot take place when such inferiority complexes, that helped produce such relations in the first place, are still operative. Fanon saw that for the oppressed to “turn away” from their master-dependency would be necessary, to allow for the struggle for freedom and equality to be on their own terms and values. Therefore, Fanon advocated for such self-recognition and for communities to turn inward to allow for the individual and collective revaluation of their culture and identity, so that “if approached critically and directed appropriately, [they] could help jolt the colonized into an ‘actional’ existence, as opposed to a ‘reactional’ one characterized by ressentiment”.[61] Robert Young highlights the power of such self-recognition through noting that in the context and process of the decolonisation of the ‘third world’ it was the process of collective self-affirmation and self-recognition that led many colonised groups to develop a “distinctive postcolonial epistemology and ontology”[62], thus enabling them to begin to comprehend and construct alternative social orders to that of colonial project. Violence With regards to Fanon’s proposed second means of decolonisation, namely the use of violence, such a method is met with clear hesitation. However, Fanon’s exploration of why violence is necessary is compelling, particularly when one understands the intricacies of the context and power balances at play. In his book Wretched of the Earth, Fanon concluded that “decolonisation is always a violent phenomenon”.[63] This statement came from Fanon’s experiences, observation and reflections from the Albanian War of Independence, from which he concluded that non-violent resistance only leads to the preservation of a capitalist, colonialist state, as “violence is the only language spoken by the colonist”[64] and therefore violence, i.e the language of the colonist is the only way feasible way to be able respond to an inherently violent system.[65] Fanon argues that colonialism and its maintenance depend on violence with the colonisers’ and natives’ “first encounter… marked by violence”.[66] Furthermore, as already stated, the colonial regime depends on power imbalance and subjugation of colonial subjects, with whom they have no interest in engaging in reasoned or emotional discourse.[67] Therefore, violence and the colonial regime cannot be separated, even with the most arguably ‘passive’ form of coloniality, violence was still present. For example, the ‘hearts and minds’ programme instilled in the Vietnam War, though prescribed to simply help win the support of Vietnamese people to assist in winning the war, but in reality, used non passive tactics such as forced relocation.[68] Paul Dixon highlights how the counter-insurgency methods used were deemed by the ‘colonists’ to be advantageous examples of ‘minimum force[69]’. Such an example explicitly highlights that even in cases of ‘passive’ versions of colonialism, repression and brutality is still used, thus supporting Fanon’s argument that the colonial system is dependent on violence. Therefore, Fanon argues that violence is the only feasible avenue for actual and substantial decolonisation to occur, the terms of such can never be in that of the coloniser or those in power,[70] thus resulting in the necessity for violence. Furthermore, he argues this violence is not to be arbitrary, but only proportional for the allowance for radical change and the overthrowing of repressive regimes that rely on both the psychological violence highlighted previously, but also physical violence.[71] However, despite such observations, it is important to question as to whether such an approach is still compatible within a contemporary context. To illustrate such a query, we can look to observations made by Priyamvada Gopal in relation to Maoists in India’s central regions and their struggle for autonomy from India, where she noted that such struggles for autonomy were seen as a colonial struggle against a colonial power that fed through ‘democracy.[72] Here Gopal notes that neither peaceful nor violent methods of anti-colonial struggles worked, as either their peacefulness was overlooked or their violence against what they believed to be the ‘colonial regime’ did not lead to any substantial change.[73] Here lies my main qualm with the application of Fanon’s second approach to his anti-colonial methodology, namely that it assumes that what is generally understood as ‘de-colonialism’ is always possible. By this I argue that in a contemporary context, the ‘colonial regime’ is not as accessible nor explicit as it used to be. This is due to the fact that the remains of colonialism is now much more subtle than an overt empire due to drastic changes in the structure and meaning of coloniality and colonial states, meaning it is more difficult to see how violence or non-violence could be beneficial, when the target of such violence is less clear cut and accessible and therefore as Kandalla Balagopal notes, ‘you can hold a gun against a landlord, but not the Indo-US Nuclear Deal’[74]. However, despite this I would still argue that Fanon was justified to state that as colonialism and its sustainment is dependent on violence, a form of violence will be necessary to dismantle it. However, in a contemporary context it is hard to identify what form of violence will be necessary for the reasons previously noted, however I would still stand by Fanon’s dualled mechanism approach as, as already mentioned, self-recognition only lays the foundations for decolonisation thus still necessitating for another mechanism to affect decolonisation as opposed to just the mindset. Overall, it is reasonable to appreciate that social struggles born out of colonialism can be based on misrecognition. However, to suggest that such effects can be solved largely by the Politics of Recognition would be to disregard the distinct and intersecting issues of power that are at play in such a context. Furthermore, such an approach undermines the necessity and power that self-recognition can have. Therefore, one advantageous mechanism for the amelioration of colonialisms effects, is as mentioned, self-recognition in that through this process such individuals are able to define and understand themselves on their own terms and thus be able to begin to interact and dismantle with the systems of power at play. [1] Throughout this essay I will be using ‘post-colonialism’ and ‘decolonisation’ interchangeably to refer to the operative time period and efforts of dismantling colonialisms effects, retrospectively, [2] Monique McIntosh, Essay Plan, 11/03/22. [3] Hegel GWF, Georg Wilhelm Friedrich Hegel: The Phenomenology of Spirit (Terry Pinkard and Michael Baur eds Cambridge University Press 2018). [4] Robert C Solomon, Continental Philosophy Since 1750: The Rise and Fall of the Self (OUP 1988). [5] Charles Taylor ‘The Politics of Recognition’ in Multiculturalism: Examining the politics of recognition (PUP 1994). [6] Samantha Balaton-Chrimes & Victoria Stead ‘Recognition, power and coloniality’ [2017] Postcolonial Studies 6. [7] ibid. [8] ibid. [9] Taylor (n 5) 3. [10] Paddy McQueen, Subjectivity, Gender and the Struggle for Recognition (Palgrave Macmillan 2015) 46. [11] ibid. [12] Cillian McBride, Recognition (Polity 2013) 6. [13] Bert van den Brink, Recognition and Power: Axel Honneth and the Tradition of Critical Social Theory (CUP 2010). [14] Audre Lorde, ‘The Personal and the Political Panel’ (Second Sex Conference, 29th October 1979) < https://monoskop.org/images/2/2b/Lorde_Audre_1983_The_Masters_Tools_Will_Never_Dismantle_the_Masters_House.pdf> accessed 25th March. [15] Glen Sean Coulthard, Red Skin, White Masks: Rejecting the Colonial Politics of Recognition (University of Minnesota Press, 2014). [16] Fanon Black Skin, White Masks (Pluto Press 1986). [17] Coulthard (n 16). [18] ibid. [19] ibid. [20] ibid. [21] ibid. [22] ibid 11. [23] ibid. [24] (1997), 3 SCR 1010. [25] Coulthard (n 16) 12. [26] ibid. [27] Ibid. [28] Sartre, Anti-Semite and Jew: An Exploration of the Etiology of Hate (New York: Schocken Books, 1974) [29] Coulthard (n 16) 3. [30] ibid. [31] ibid. [32] ibid. [33] Ibid. [34] Balaton-Chrimes, S. and Staed, V. ‘Recognition, Power and Coloniality’, Postcolonial Studies 20/1 (2017) 7. [35] Dale Turner, This Is Not a Peace Pipe: Towards a Critical Indigenous Philosophy (Toronto: University of Toronto Press, 2006) 5. [36] ibid. [37] ibid. [38] ibid. [39] See Coulthard (n 16) 14. [40] ibid. [41] See Coulthard (n 16) 14. A similar stance held by Franz Fanon that will be addressed in a later section. [42] ibid 15. [43] ibid. [44] ibid. [45] Axel Honneth and Nancy Fraser, Redistribution or Recognition? (Verso 2003). [46] ibid. [47] Fraser, N. ‘Rethinking Recognition’ New Left Review 3 (2000) [48] ibid. [49] ibid. [50] Patchen Markell ‘Recognition and Redistribution’, The Oxford Handbook of Political Theory (OUP 2009). [51] ibid. [52] ibid. [53] Fanon (n 18). [54] Coulthard (n 16) 140. [55] ibid. [56] ibid. [57] ibid. [58] ibid 141. [59] ibid. [60] Fanon (n 18). [61] Coulthard (n 16) 150. [62] ibid. [63] Fanon (first published 1961, Grove Atlantic, 2021). [64] ibid. [65] ibid 66. [66] ibid 28. [67] Ibid. [68] Paul Dixon, ‘‘Hearts and Minds’? British Counter Insurgency from Malaya to Iraq” [2009] Journal of Strategic Studies 353. [69] ibid. [70] Fanon (n 70). [71] ibid. [72] Priyamvada Gopal, ‘Concerning Maoism: Fanon, Revolutionary Violence, and Postcolonial India’ [2013] South Atlantic Quarterly 115. [73] ibid 117. [74] ibid 125.